2020
DOI: 10.1002/eat.23240
|View full text |Cite
|
Sign up to set email alerts
|

Suicide attempts requiring hospitalization in patients with eating disorders: A retrospective cohort study

Abstract: Objective: Suicide attempts requiring hospitalization are known to be common in patients who are diagnosed with eating disorders. Attempting suicide is a major indicator for those at risk of completed suicide. Both the specific eating disorder diagnosis and the influence of psychiatric comorbidities on suicide attempts requiring hospitalization were investigated, with demographic and socioeconomic variables as confounders, over a 10-year observation period from These data include all diagnoses for inpatient ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 36 publications
1
20
0
3
Order By: Relevance
“…Our study has several limitations, including: (1) reliance on several prevalence studies using varying estimation techniques, which may have led to uncertain estimates across age groups; (2) an inability to comprehensively control for all confounding factors, and in particular comorbidities, which are common among individuals with eating disorders—for example, some premature mortality costs may occur due to comorbid psychiatric illness among individuals with eating disorders (Cliffe et al, 2020); (3) the utilization of average group effects across all model inputs (there is inherent variability in costs across individuals and systems in the U.S. that no existing datasets could comprehensively address for the purposes of our study); (4) other limitations in the available epidemiological data precluded a comprehensive analysis of costs across all eating disorder diagnostic groups or major demographic groups (e.g., data on avoidant restrictive food intake disorder are lacking although it has been attracting increasing research attention; see Bourne, Bryant‐Waugh, Cook, & Mandy, 2020); and (5) our inability to estimate costs associated with the longer‐term physical and psychological health sequelae of eating disorders that persist or emerge over time (e.g., reproductive or obstetric complications, osteoporosis, gastrointestinal dysfunction or cancers, etc. ; Mantel, Hirschberg, & Stephansson, 2020; Thornton et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Our study has several limitations, including: (1) reliance on several prevalence studies using varying estimation techniques, which may have led to uncertain estimates across age groups; (2) an inability to comprehensively control for all confounding factors, and in particular comorbidities, which are common among individuals with eating disorders—for example, some premature mortality costs may occur due to comorbid psychiatric illness among individuals with eating disorders (Cliffe et al, 2020); (3) the utilization of average group effects across all model inputs (there is inherent variability in costs across individuals and systems in the U.S. that no existing datasets could comprehensively address for the purposes of our study); (4) other limitations in the available epidemiological data precluded a comprehensive analysis of costs across all eating disorder diagnostic groups or major demographic groups (e.g., data on avoidant restrictive food intake disorder are lacking although it has been attracting increasing research attention; see Bourne, Bryant‐Waugh, Cook, & Mandy, 2020); and (5) our inability to estimate costs associated with the longer‐term physical and psychological health sequelae of eating disorders that persist or emerge over time (e.g., reproductive or obstetric complications, osteoporosis, gastrointestinal dysfunction or cancers, etc. ; Mantel, Hirschberg, & Stephansson, 2020; Thornton et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…In fact, in the national US epidemiologic survey, between 17–45% reported a suicide attempt before the onset of their EDs (Udo et al, 2019). Possible explanations for this co‐occurrence include comorbid psychiatric disorders such as depression, bipolar disorder, and substance abuse (Cliffe et al, 2020; Franko & Keel, 2006; Smith, Zuromski, et al, 2018), psychological and personality traits (Bulik et al, 2008; Milos et al, 2004; Pisetsky et al, 2015), self‐image (Andersén & Birgegård, 2017), early cognitive schema (Portzky, van Heeringen, & Vervaet, 2014), interoceptive deficits (Smith, Forrest, & Velkoff, 2018), alexithymia (Carano et al, 2012), and impulsivity (Sagiv & Gvion, 2020). Some of these traits are subsumed under the multidimensional concept of emotion dysregulation (Gratz & Roemer, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…This way, we followed procedures used by other published studies in the field. 79 81 However, even when following standardised procedures, in many cases we were not able to distinguish between SA and NSSI. In the records, we found that the attending clinicians had difficulties to make this distinction and did not always agree.…”
Section: Limitationsmentioning
confidence: 92%